Standardized Monitoring in Online English Learning: Integrating Context, Pedagogical Pillars, and Monitoring Phases - Karin Sari Saputra; Sisilia Setiawati Halimi; Harwintha Yuhria Anjarningsih (Journal of Education and Teaching (JET), 2026)
Monitoring in online English education remains inconsistently defined and often treated as an administrative routine rather than a pedagogical process. This paper addresses that gap by proposing the Standardized Monitoring Framework (SMF)—a theoretically grounded model that integrates monitoring with instruction to enhance quality and engagement. Built through a conceptual synthesis of Learning-Oriented Assessment (LoLA), formative feedback, and digital engagement theories, the SMF establishes five pedagogical pillars: Targeted Content Delivery, Diverse Assessment Strategies, Personalized Formative Feedback, Engagement Optimization, and Comprehensive Learning Evaluation. These pillars operate across four monitoring phases—Preparation, Exploration, Adjustment, and Mastery—supported by three contextual domains of learning foundations, human-centered dynamics, and the instructional monitoring cycle. Drawing illustrative insights from the Elingway platform, the study demonstrates how SMF bridges theory and practice to promote responsive, autonomous, and sustained learning in non-metropolitan digital contexts. The paper concludes by highlighting the framework’s theoretical novelty and its potential for empirical validation in future studies.